Odpowiedzi

2010-03-18T20:16:03+01:00
-4x+2=x/3
6/15-2/5x=-2
2x+2/9-1/3=2x+5/9
alej nie wiem sorry
Najlepsza Odpowiedź!
2010-03-18T20:23:01+01:00
1.)

-2(2x-1)=x/3
-4x+2=x/3 |*3
-12x+6=x
x=-12x+6 |+12x
13x=6 |:13
x=6/13

2.)

zamiana ułamku zwykłego na dziesiętny: 2/5=0,4
0,4*(3-x)=-2
1,2-0,4x=-2 |-1,2
-0,4x=-3,2 |:(-0,4)
x=8

3.)

x+2/9 + x-1/3=1
2x+ 2/9 - 3/9=1
2x - 1/9 =1 |+1/9
2x=1 1/9 |:2
x= 5/9

4.)

2x+ 3/5 = 2-x/3+x |*3
6x+1,8=6-x+3x |-1,8
6x=4,2+2x |-2x
4x=4,2 |:4
x=1,05

5.)

3x-5/2 - 5x-1/10 =0
-2x-2,4=0 |+2,4
-2x=2,4 |:(-2)
x=(-1,2)
1 5 1